Relationships among Service Quality, Customer Satisfaction and Customer Loyalty in Chain Restaurant - Tu, Yu-Te; ., Yu-Yi Chang (Information Management and Business Review, 2011)
Chain restaurant is one of the fastest growing restaurants in the food service industry. In America, Service industry contributes about 60% of the annual GDP and 70% of new jobs. According to the statistics of Executive Yuan of Taiwan, the service industry contributes over 70% of the annual GDP in 2008. The ultimate goal for companies is to build customer loyalty. With loyal customers, companies can reduce the operating cost and acquisition expenses. An improvement of 5 percent in customer retention leads to an increase of 25 percent to 75 percent in profit. It costs more than five times as much to obtain a new customer than to keep an existing one. This initial study was from relevant literature, then set up research structure and hypotheses. Survey was employed, and respondents were from the customers of Taoban in Taiwan. There were 182 usable questionnaires to analyze descriptive statistics, reliability, validity, and SEM model. The research found that service quality significantly affects customer satisfaction, and customer satisfaction has strong impact on customer loyalty for the sample. Therefore, firms have to specifically focus on these factors in order to build a long-term and mutually profitability relationship with a customer and create loyalty as competitive advantages in the market.